Environment-friendly polymer cement waterproof coating and preparation method thereof

By using inorganic modified materials and functional composites in polymer cement waterproof coatings, combined with modified sepiolite, the problem of poor UV resistance of existing coatings is solved, and higher waterproof performance and service life are achieved.

CN119432181AActive Publication Date: 2025-02-14佛山市德堡建材有限公司
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411727878.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing polymer cement waterproof coatings have poor UV resistance and are susceptible to UV influence, causing the coating to crack, break or even fall off, and shorten their service life.

Method used

An environmentally friendly polymer cement waterproof coating consisting of liquid and powder with a mass ratio of 1:0.8-1.1, is used. Inorganic modified materials and functional composites are added to the liquid material, and an ultraviolet-resistant amine group is introduced into the functional composite. Add modified sepiolite to the powder to improve waterproofing performance.

Benefits of technology

It significantly improves the UV resistance and waterproof properties of waterproof coatings, extends service life, and avoids early aging and damage of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432181A_ABST
    Figure CN119432181A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of waterproof coatings, and discloses an environment-friendly polymer cement waterproof coating and a preparation method thereof.The environment-friendly polymer cement waterproof coating is composed of a liquid material and a powder material according to the mass ratio of 1: 0.8-1.1, and the liquid material is prepared from acrylic emulsion, a coalescing agent, a defoaming agent, an inorganic modified material, a functional compound and water; the powder material comprises the following raw materials: cement, quartz sand, ground calcium carbonate, sodium stearate, wollastonite and a water reducing agent; by adding the inorganic modified material, the prepared waterproof coating has excellent waterproof performance, a water molecule diffusion path is prolonged, and water molecule permeation is effectively delayed; by adding the functional compound, the prepared waterproof coating has excellent bonding strength and ultraviolet resistance, can be tightly combined with a bonded base material, can still keep stable performance under long-term ultraviolet irradiation, and has long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof coatings, and in particular to an environmentally friendly polymer cement waterproof coating and a preparation method thereof. Background Art

[0002] With the development of society and the advancement of science and technology, the number of engineering construction projects has gradually increased, and higher requirements have been placed on the waterproof coatings of buildings. Polymer cement waterproof coatings are environmentally friendly and waterproof building materials. They are mainly composed of liquid materials composed of high molecular polymer emulsions and various additives and powder materials composed of cement and various additives. They are generally applied to the surface of the building base to form a waterproof coating with the rigidity of inorganic powders and the flexibility of high molecular organic liquids. It has the advantages of fast drying speed, excellent physical properties and good environmental protection. The coating is used to prevent moisture from penetrating from small gaps to meet waterproofing needs.

[0003] The polymer emulsion used in polymer cement waterproof coating liquid generally uses acrylic emulsion, ethylene-vinyl acetate copolymer emulsion, acrylate emulsion and the like as main raw materials. Acrylic emulsion has excellent processing performance, rheological properties and thermal stability. It is an excellent polymer emulsion and can be used to prepare polymer cement waterproof coating. However, acrylic emulsion has poor UV resistance. When waterproof coating prepared by acrylic emulsion is exposed to ultraviolet rays during use, the polymer chain will break, resulting in aging and degradation of the coating, cracking, damage and even falling off. Long-term erosion by water vapor or rain will also cause the coating to break and fall off, greatly shortening the service life of the waterproof coating. The patent with publication number CN116004073B discloses a polymer cement waterproof coating, which includes a liquid modified acrylic ester emulsion and a powder silicate cement, a filler, and tannic acid. By mixing the liquid and the powder, a highly cross-linked and dense waterproof film layer can be obtained, which improves the water resistance of the polymer cement waterproof coating. However, the patent does not take into account that the polymer cement waterproof coating has poor UV resistance and is easily affected by ultraviolet rays, causing the coating to crack and fall off. Therefore, the present invention provides an environmentally friendly polymer cement waterproof coating with excellent waterproof and UV resistance, a long service life, and broad application prospects. Summary of the invention

[0004] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide an environmentally friendly polymer cement waterproof coating and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An environmentally friendly polymer cement waterproof coating is composed of a liquid material and a powder material in a mass ratio of 1:0.8-1.1, wherein the liquid material comprises the following raw materials in parts by weight: 80-100 parts of acrylic emulsion, 3-6 parts of film-forming aid, 1-4 parts of defoamer, 3-6 parts of inorganic modified material, 5-8 parts of functional composite, and 14-24 parts of water; and the powder material comprises the following raw materials in parts by weight: 10-35 parts of cement, 10-30 parts of quartz sand, 25-55 parts of heavy calcium carbonate, 2-6 parts of sodium stearate, 10-15 parts of wollastonite, and 1-4 parts of water reducer.

[0007] Furthermore, the film-forming aid is lauryl alcohol ester; the defoaming agent is polydimethylsiloxane; the cement is No. 32.5 white silicate cement or No. 32.5 gray silicate cement; the particle size of the quartz sand is 120-200 mesh; the particle size of the heavy calcium carbonate is 200-400 mesh; and the water reducer is a naphthalene-based water reducer or a polycarboxylic acid water reducer.

[0008] Furthermore, the preparation method of the inorganic modified material comprises the following steps:

[0009] Step A: adding sepiolite into dimethyl sulfoxide, dispersing evenly, raising the temperature to 90-100° C., adding 2,2-bis(4-carboxyphenyl)hexafluoropropane and a catalyst, mixing evenly, reacting for 3-5 hours, filtering, washing, and drying to obtain modified sepiolite;

[0010] Step B: Add the modified sepiolite to N,N-dimethylformamide, stir and mix evenly, then add 2-(tert-butyldimethylsilyloxy)ethylamine, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, react at room temperature for 4-6 hours, separate the product, wash and dry to obtain an inorganic modified material.

[0011] By adopting the above technical scheme, the surface of the sepiolite contains abundant hydroxyl groups, which can undergo esterification reaction with the carboxyl groups in the structure of 2,2-bis(4-carboxyphenyl)hexafluoropropane under the action of high temperature and catalyst, thereby introducing carboxyl groups on the surface of the sepiolite to obtain modified sepiolite. Under the action of dicyclohexylcarbodiimide and 4-dimethylaminopyridine, the carboxyl groups on the surface of the modified sepiolite can undergo amidation reaction with the amino groups in the structure of 2-(tert-butyldimethylsilyloxy)ethylamine to obtain an inorganic modified material.

[0012] Furthermore, in step A, the catalyst is p-toluenesulfonic acid.

[0013] Furthermore, the preparation method of the functional complex comprises the following steps:

[0014] Step S1: adding polytetrahydrofuran ether diol to tetrahydrofuran, mixing evenly, introducing nitrogen protection, adding halogenated acid chloride modifier and promoter, stirring and reacting for 3-5h, removing the solvent by vacuum distillation, discharging, and obtaining an intermediate substance;

[0015] Step S2: adding the intermediate substance to dimethyl sulfoxide, stirring and mixing evenly, introducing nitrogen protection, raising the temperature to 70-80° C., adding 2,2,6,6-tetramethylpiperidinol and potassium carbonate, reacting for 4-5 hours, cooling to room temperature, discharging, and obtaining a functional complex.

[0016] By adopting the above technical scheme, the hydroxyl group in the structure of polytetrahydrofuran ether diol can react with the acyl chloride in the structure of the halogenated acyl chloride modifier under the action of a promoter, thereby obtaining an intermediate substance with a halogen substituent. Under the action of potassium carbonate, the halogen substituent in the structure of the intermediate substance can undergo a substitution reaction with the hydroxyl group in the structure of 2,2,6,6-tetramethylpiperidinol, thereby obtaining a functional complex.

[0017] Furthermore, in step S1, the halogenated acyl chloride modifier is any one of chloroacetyl chloride, bromoacetyl chloride or 3-chloropropionyl chloride.

[0018] Furthermore, in step S1, the promoter is triethylamine or pyridine.

[0019] A method for preparing an environmentally friendly polymer cement waterproof coating comprises the following steps:

[0020] Step 1: Add acrylic emulsion into water, mix well, add film-forming aid, defoamer, inorganic modifier, functional compound, start stirring, set the stirring rate to 100-300r / min, stir for 15-45min, and obtain liquid material;

[0021] Step 2: Mix cement, quartz sand, heavy calcium carbonate, sodium stearate, wollastonite and water reducer evenly, start stirring, set the stirring rate to 200-400r / min, stir for 10-40min, and obtain powder;

[0022] Step 3: Add liquid and powder in a mass ratio of 1:0.8-1.1 into a high-speed mixer, set the stirring rate to 150-350r / min, and stir for 10-35min to obtain an environmentally friendly polymer cement waterproof coating.

[0023] Beneficial effects of the present invention:

[0024] (1) The inorganic modified material prepared by the present invention uses sepiolite as a matrix. By organically modifying the sepiolite, the compatibility between the inorganic modified material and the polymer emulsion is improved, thereby avoiding agglomeration in the polymer emulsion, and promoting the inorganic modified material to be evenly dispersed in the coating, thereby improving the interface bonding force and intermolecular cohesion between the sepiolite and the polymer emulsion, thereby improving the density of the coating. At the same time, sepiolite has a layered structure and is evenly dispersed in the coating to form a multi-layer barrier structure, which can extend the diffusion path of water molecules and effectively delay the penetration of water molecules. In addition, the introduction of rigid benzene rings, fluorine-containing chain segments and tert-butyl groups with hydrophobic effects on the surface of the sepiolite can effectively reduce the surface energy of the sepiolite, further prevent the penetration of water molecules, and greatly improve the waterproof performance of the coating.

[0025] (2) The functional composite prepared by the present invention can be cross-linked with the polymer emulsion to form a polymer network structure, which makes the cohesion stronger. The ether bonds in the functional composite structure can improve the flexibility of the coating, so that the waterproof coating can better adapt to small deformations. On the other hand, it can promote the combination between the polymer and the powder, improve the adhesion between the coating and the substrate, and improve the bonding strength. At the same time, a hindered amine group with anti-ultraviolet effect is introduced into the functional composite structure by chemical bonding. By absorbing ultraviolet rays, capturing free radicals, and reacting with free radicals, the coating is protected from ultraviolet erosion. The migration and precipitation of small molecule anti-ultraviolet substances are also avoided, resulting in a decrease in the anti-ultraviolet performance in the later stage, and the coating cracks, breaks, or even falls off under the action of ultraviolet rays, thereby extending the service life of the waterproof coating.

[0026] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0028] Figure 1 It is the infrared spectrum of the inorganic modified material in the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The preparation methods of the inorganic modified materials and composite additives in the following examples and comparative examples are as follows:

[0031] 1. Preparation of inorganic modified materials

[0032] Step A: 3.6 g of sepiolite was added to dimethyl sulfoxide, and after being evenly dispersed, the temperature was raised to 95° C., 1.8 g of 2,2-bis(4-carboxyphenyl)hexafluoropropane and 0.5 g of p-toluenesulfonic acid were added, and the mixture was evenly mixed. After reacting for 4 h, the mixture was filtered, washed, and dried to obtain modified sepiolite;

[0033] Step B: Add 3.4 g of modified sepiolite to N,N-dimethylformamide, mix and stir evenly, then add 1.5 g of 2-(tert-butyldimethylsilyloxy)ethylamine, 0.3 g of dicyclohexylcarbodiimide and 0.1 g of 4-dimethylaminopyridine, react at room temperature for 5 hours, separate the product, wash and dry to obtain an inorganic modified material.

[0034] The inorganic modified materials were tested by Fourier infrared spectrometer, such as Figure 1 As shown in the figure, analysis shows that in the infrared spectrum of inorganic modified materials, 3032cm -1 The absorption peak of the carbon-hydrogen bond in the benzene ring appeared at 1745 cm -1 The absorption peak of the carbon-oxygen double bond in the ester group appeared at 1660 cm -1 The absorption peak of the carbon-oxygen double bond in the amide bond appeared at 1367 cm -1 The absorption peak of tert-butyl appeared at 1246 cm -1 The absorption peak of carbon-fluorine bond appeared at 1035cm -1 The absorption peak of silicon-oxygen bond appears at

[0035] 2. Preparation of composite additives

[0036] Step S1: adding 4 g of polytetrahydrofuran ether diol to tetrahydrofuran, mixing well, introducing nitrogen protection, adding 2.9 g of chloroacetyl chloride and 0.8 g of triethylamine, stirring and reacting for 5 h, removing the solvent by distillation under reduced pressure, discharging the material, and obtaining an intermediate substance;

[0037] Step S2: Add 3.5 g of the intermediate substance to dimethyl sulfoxide, stir and mix evenly, introduce nitrogen protection, raise the temperature to 75°C, add 1.6 g of 2,2,6,6-tetramethylpiperidinol and 0.5 g of potassium carbonate, react for 5 hours, cool to room temperature, discharge, and obtain a functional complex.

[0038] The organic element content of the functional complex was analyzed using a Var io ELⅢ element analyzer. The test results showed that the percentage of nitrogen in the functional complex was 4.53%. Since polytetramethylene glycol does not contain nitrogen, it can be reasonably inferred that 2,2,6,6-tetramethylpiperidinol reacted successfully with polytetramethylene glycol to provide a nitrogen source.

[0039] Example 1

[0040] Preparation of environmentally friendly polymer cement waterproof coating

[0041] Step 1: Add 80g of acrylic emulsion to 14g of water, mix well, add 3g of lauryl ester film-forming aid, 1g of polydimethylsiloxane defoamer, 3g of inorganic modified material, and 5g of functional composite, start stirring, set the stirring rate to 100r / min, stir for 15min, and obtain a liquid material;

[0042] Step 2: Mix 10g of No. 32.5 gray silicate cement, 10g of quartz sand with a particle size of 120 mesh, 25g of heavy calcium carbonate with a particle size of 200 mesh, 2g of sodium stearate, 10g of wollastonite, and 1g of polycarboxylate water reducer, start stirring, set the stirring rate to 200r / min, and stir for 10 minutes to obtain a powder;

[0043] Step 3: Add liquid and powder in a mass ratio of 1:0.8 into a high-speed mixer, set the stirring rate to 150r / min, and stir for 10 minutes to obtain an environmentally friendly polymer cement waterproof coating.

[0044] Example 2

[0045] Preparation of environmentally friendly polymer cement waterproof coating

[0046] Step 1: Add 85g of acrylic emulsion to 16g of water, mix well, add 4g of lauryl ester film-forming aid, 2g of polydimethylsiloxane defoamer, 4g of inorganic modified material, and 6g of functional composite, start stirring, set the stirring rate to 150r / min, stir for 25min, and obtain a liquid material;

[0047] Step 2: Mix 20g of No. 32.5 gray silicate cement, 14g of quartz sand with a particle size of 160 mesh, 35g of heavy calcium carbonate with a particle size of 300 mesh, 4g of sodium stearate, 12g of wollastonite, and 2g of polycarboxylate water reducer, start stirring, set the stirring rate to 250r / min, and stir for 20min to obtain powder;

[0048] Step 3: Add liquid and powder in a mass ratio of 1:0.9 into a high-speed mixer, set the stirring rate to 200r / min, and stir for 20 minutes to obtain an environmentally friendly polymer cement waterproof coating.

[0049] Example 3

[0050] Preparation of environmentally friendly polymer cement waterproof coating

[0051] Step 1: Add 90g of acrylic emulsion to 18g of water, mix well, add 4g of lauryl ester film-forming aid, 2g of polydimethylsiloxane defoamer, 5g of inorganic modified material, and 7g of functional composite, start stirring, set the stirring rate to 200r / min, stir for 35min, and obtain a liquid material;

[0052] Step 2: Mix 30g of No. 32.5 gray silicate cement, 20g of quartz sand with a particle size of 180 mesh, 45g of heavy calcium carbonate with a particle size of 350 mesh, 5g of sodium stearate, 14g of wollastonite, and 3g of polycarboxylate water reducer, start stirring, set the stirring rate to 300r / min, and stir for 30min to obtain powder;

[0053] Step 3: Add the liquid and powder in a mass ratio of 1:1 into a high-speed mixer, set the stirring rate to 250r / min, and stir for 30 minutes to obtain an environmentally friendly polymer cement waterproof coating.

[0054] Example 4

[0055] Preparation of environmentally friendly polymer cement waterproof coating

[0056] Step 1: Add 100g of acrylic emulsion to 24g of water, mix well, add 6g of lauryl ester film-forming aid, 4g of polydimethylsiloxane defoamer, 6g of inorganic modified material, and 8g of functional composite, start stirring, set the stirring rate to 300r / min, stir for 45min, and obtain a liquid material;

[0057] Step 2: Mix 35g of No. 32.5 gray silicate cement, 30g of quartz sand with a particle size of 200 mesh, 55g of heavy calcium carbonate with a particle size of 400 mesh, 6g of sodium stearate, 15g of wollastonite, and 4g of polycarboxylate water reducer, start stirring, set the stirring rate to 400r / min, and stir for 40min to obtain powder;

[0058] Step 3: Add liquid and powder in a mass ratio of 1:1.1 into a high-speed mixer, set the stirring rate to 350r / min, and stir for 35 minutes to obtain an environmentally friendly polymer cement waterproof coating.

[0059] Comparative Example 1

[0060] Preparation of environmentally friendly polymer cement waterproof coating

[0061] Step 1: Add 90g of acrylic emulsion to 18g of water, mix well, add 4g of lauryl ester film-forming aid, 2g of polydimethylsiloxane defoamer, and 5g of inorganic modified material, start stirring, set the stirring rate to 200r / min, stir for 35min, and obtain a liquid material;

[0062] Step 2: Mix 30g of No. 32.5 gray silicate cement, 20g of quartz sand with a particle size of 180 mesh, 45g of heavy calcium carbonate with a particle size of 350 mesh, 5g of sodium stearate, 14g of wollastonite, and 3g of polycarboxylate water reducer, start stirring, set the stirring rate to 300r / min, and stir for 30min to obtain powder;

[0063] Step 3: Add the liquid and powder in a mass ratio of 1:1 into a high-speed mixer, set the stirring rate to 250r / min, and stir for 30 minutes to obtain an environmentally friendly polymer cement waterproof coating.

[0064] Comparative Example 2

[0065] Preparation of environmentally friendly polymer cement waterproof coating

[0066] Step 1: Add 90g of acrylic emulsion to 18g of water, mix well, add 4g of lauryl ester film-forming aid, 2g of polydimethylsiloxane defoamer, and 7g of functional compound, start stirring, set the stirring rate to 200r / min, stir for 35min, and obtain a liquid material;

[0067] Step 2: Mix 30g of No. 32.5 gray silicate cement, 20g of quartz sand with a particle size of 180 mesh, 45g of heavy calcium carbonate with a particle size of 350 mesh, 5g of sodium stearate, 14g of wollastonite, and 3g of polycarboxylate water reducer, start stirring, set the stirring rate to 300r / min, and stir for 30min to obtain powder;

[0068] Step 3: Add the liquid and powder in a mass ratio of 1:1 into a high-speed mixer, set the stirring rate to 250r / min, and stir for 30 minutes to obtain an environmentally friendly polymer cement waterproof coating.

[0069] Comparative Example 3

[0070] Preparation of environmentally friendly polymer cement waterproof coating

[0071] Step 1: Add 90g of acrylic emulsion to 18g of water, mix well, add 4g of lauryl ester film-forming aid, 2g of polydimethylsiloxane defoamer, 5g of sepiolite, and 7g of functional compound, start stirring, set the stirring rate to 200r / min, stir for 35min, and obtain a liquid material;

[0072] Step 2: Mix 30g of No. 32.5 gray silicate cement, 20g of quartz sand with a particle size of 180 mesh, 45g of heavy calcium carbonate with a particle size of 350 mesh, 5g of sodium stearate, 14g of wollastonite, and 3g of polycarboxylate water reducer, start stirring, set the stirring rate to 300r / min, and stir for 30min to obtain powder;

[0073] Step 3: Add the liquid and powder in a mass ratio of 1:1 into a high-speed mixer, set the stirring rate to 250r / min, and stir for 30 minutes to obtain an environmentally friendly polymer cement waterproof coating.

[0074] Comparative Example 4

[0075] Preparation of environmentally friendly polymer cement waterproof coating

[0076] Step 1: Add 90g of acrylic emulsion to 18g of water, mix well, add 4g of lauryl ester film-forming aid, 2g of polydimethylsiloxane defoamer, 5g of inorganic modifier, 7g of 2,2,6,6-tetramethylpiperidinol, start stirring, set the stirring rate to 200r / min, stir for 35min, and obtain a liquid material;

[0077] Step 2: Mix 30g of No. 32.5 gray silicate cement, 20g of quartz sand with a particle size of 180 mesh, 45g of heavy calcium carbonate with a particle size of 350 mesh, 5g of sodium stearate, 14g of wollastonite, and 3g of polycarboxylate water reducer, start stirring, set the stirring rate to 300r / min, and stir for 30min to obtain powder;

[0078] Step 3: Add the liquid and powder in a mass ratio of 1:1 into a high-speed mixer, set the stirring rate to 250r / min, and stir for 30 minutes to obtain an environmentally friendly polymer cement waterproof coating.

[0079] Performance Testing

[0080] With reference to the standard GB / T 23445-2009 "Polymer Cement Waterproof Coating", the environmentally friendly polymer cement waterproof coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were tested for water impermeability, impermeability and bonding strength. The waterproof coatings were placed for 6 months and then cured to form a coating. The appearance changes of the coatings after being treated with ultraviolet rays for 7 days were tested. The test results are shown in the following table:

[0081]

[0082] It can be seen from the above table that the environmentally friendly polymer cement waterproof coating prepared by the present invention has excellent waterproof performance, bonding strength and anti-ultraviolet performance. Comparative Example 1 adds an inorganic modifier but does not add a functional composite, and the waterproof performance of the waterproof coating is excellent but the bonding strength and anti-ultraviolet performance are poor; Comparative Example 2 adds a functional composite but does not add an inorganic modifier, and the bonding strength and anti-ultraviolet performance are excellent but the waterproof performance is poor; Comparative Example 3 adds sepiolite and a functional composite, sepiolite is easy to agglomerate, and is not modified by hydrophobic benzene rings, fluorine-containing segments and tert-butyl groups, and the waterproof performance is poor, but the bonding strength and anti-ultraviolet performance are excellent; Comparative Example 4 adds an inorganic modifier and 2,2,6,6-tetramethylpiperidinol, and the waterproof performance is excellent, but 2,2,6,6-tetramethylpiperidinol is easy to migrate and precipitate, resulting in a decrease in anti-ultraviolet performance, so the bonding strength and anti-ultraviolet performance are poor.

[0083] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. An environmentally friendly polymer cement waterproof coating, characterized in that: The invention is composed of liquid and powder in a mass ratio of 1:0.8-1.1, wherein the liquid comprises the following raw materials in parts by weight: 80-100 parts of acrylic emulsion, 3-6 parts of film-forming aid, 1-4 parts of defoamer, 3-6 parts of inorganic modified material, 5-8 parts of functional composite and 14-24 parts of water; and the powder comprises the following raw materials in parts by weight: 10-35 parts of cement, 10-30 parts of quartz sand, 25-55 parts of heavy calcium carbonate, 2-6 parts of sodium stearate, 10-15 parts of wollastonite and 1-4 parts of water reducer.

2. The environmentally friendly polymer cement waterproof coating according to claim 1, characterized in that: The film-forming aid is lauryl alcohol ester; the defoaming agent is polydimethylsiloxane; the cement is No. 32.5 white silicate cement or No. 32.5 gray silicate cement; the particle size of the quartz sand is 120-200 mesh; the particle size of the heavy calcium carbonate is 200-400 mesh; the water reducer is a naphthalene-based water reducer or a polycarboxylic acid water reducer.

3. The environmentally friendly polymer cement waterproof coating according to claim 1, characterized in that: The preparation method of the inorganic modified material comprises the following steps: Step A: adding sepiolite into dimethyl sulfoxide, dispersing evenly, raising the temperature to 90-100° C., adding 2,2-bis(4-carboxyphenyl)hexafluoropropane and a catalyst, mixing evenly, reacting for 3-5 hours, filtering, washing, and drying to obtain modified sepiolite; Step B: Add the modified sepiolite to N,N-dimethylformamide, stir and mix evenly, then add 2-(tert-butyldimethylsilyloxy)ethylamine, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, react at room temperature for 4-6 hours, separate the product, wash and dry to obtain an inorganic modified material.

4. The environmentally friendly polymer cement waterproof coating according to claim 3, characterized in that: In step A, the catalyst is p-toluenesulfonic acid.

5. The environmentally friendly polymer cement waterproof coating according to claim 1, characterized in that: The method for preparing the functional complex comprises the following steps: Step S1: adding polytetrahydrofuran ether diol to tetrahydrofuran, mixing evenly, introducing nitrogen protection, adding halogenated acid chloride modifier and promoter, stirring and reacting for 3-5h, removing the solvent by vacuum distillation, discharging, and obtaining an intermediate substance; Step S2: adding the intermediate substance to dimethyl sulfoxide, stirring and mixing evenly, introducing nitrogen protection, raising the temperature to 70-80° C., adding 2,2,6,6-tetramethylpiperidinol and potassium carbonate, reacting for 4-5 hours, cooling to room temperature, discharging, and obtaining a functional complex.

6. The environmentally friendly polymer cement waterproof coating according to claim 5, characterized in that: In step S1, the halogenated acyl chloride modifier is any one of chloroacetyl chloride, bromoacetyl chloride or 3-chloropropionyl chloride.

7. The environmentally friendly polymer cement waterproof coating according to claim 5, characterized in that: In step S1, the promoter is triethylamine or pyridine.

8. A method for preparing the environmentally friendly polymer cement waterproof coating as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Add acrylic emulsion into water, mix well, add film-forming aid, defoamer, inorganic modifier, functional compound, start stirring, set the stirring rate to 100-300r / min, stir for 15-45min, and obtain liquid material; Step 2: Mix cement, quartz sand, heavy calcium carbonate, sodium stearate, wollastonite and water reducer evenly, start stirring, set the stirring rate to 200-400r / min, stir for 10-40min, and obtain powder; Step 3: Add liquid and powder in a mass ratio of 1:0.8-1.1 into a high-speed mixer, set the stirring rate to 150-350r / min, and stir for 10-35min to obtain an environmentally friendly polymer cement waterproof coating.

Citation Information

Patent Citations

  • A polymer cement waterproof coating

    CN116004073B

  • LRRK2 kinase inhibitors

    CA2775753A1

  • Thermoplastic resin composition and molded item formed from same

    CN102869724A

  • Constructional engineering exterior wall thermal insulation material and preparation method thereof

    CN111943601A

  • Novel polymer cement waterproof coating and preparation method thereof

    CN114196274A